2015
DOI: 10.1088/0004-637x/815/2/134
|View full text |Cite
|
Sign up to set email alerts
|

SWIFT OBSERVATIONS OF GAMMA-RAY BURST PULSE SHAPES: GRB PULSE SPECTRAL EVOLUTION CLARIFIED

Abstract: We present a detailed analysis of GRB 151006A, the first GRB detected by Astrosat CZT Im-ager (CZTI). We study the long term spectral evolution by exploiting the capabilities of Fermi and Swift satellites at different phases, which is complemented by the polarization measurement with the CZTI. While the light curve of the GRB in different energy bands show a simple pulse profile, the spectrum shows an unusual evolution. The first phase exhibits a hard-to-soft (HTS) evolution until ∼ 16 − 20 s, followed by a su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 27 publications
(53 reference statements)
4
52
0
Order By: Relevance
“…Some authors also pointed out that the spectral evolution is related to the pulse profile (Hakkila & Preece 2011;Hakkila et al 2015Hakkila et al , 2018. For example, the hard-to-soft spectral evolution may primarily occur in hard and/or asymmetric pulses, and the intensity-tracking spectral evolution may be more prevalent in soft and/or symmetric pulses (Hakkila et al 2015(Hakkila et al , 2018. In addition, Hakkila & Preece (2014) found that the residuals of single pulse fits to GRB lightcurves leave behind a mysterious triple-peaked structure.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors also pointed out that the spectral evolution is related to the pulse profile (Hakkila & Preece 2011;Hakkila et al 2015Hakkila et al , 2018. For example, the hard-to-soft spectral evolution may primarily occur in hard and/or asymmetric pulses, and the intensity-tracking spectral evolution may be more prevalent in soft and/or symmetric pulses (Hakkila et al 2015(Hakkila et al , 2018. In addition, Hakkila & Preece (2014) found that the residuals of single pulse fits to GRB lightcurves leave behind a mysterious triple-peaked structure.…”
Section: Introductionmentioning
confidence: 99%
“…• Pulses evolve from hard-to-soft, with asymmetric pulses showing more pronounced spectral evolution than symmetric pulses (e.g. Crider et al (1999); Ryde & Svensson (1999); Hakkila & Preece (2011); Hakkila et al (2015)). When early pulse emission can be observed, pulses are shown to start near-simultaneously at all energies (Hakkila & Nemiroff 2009).…”
Section: Characteristics Of Grb Pulsesmentioning
confidence: 99%
“…These analyses have identified "hard-to-soft" and "intensity tracking" behaviors (e.g., Wheaton et al (1973); Golenetskii et al (1983); Norris et al (1986); Paciesas et al (1992)), but this oversimplified bimodal classification scheme has been shown to represent a continuous range of behaviors (e.g., Kargatis et al (1994); Bhat et al (1994); Ford et al (1995); Borgonovo, & Ryde (2001)). Treating each GRB pulse as a structured episode rather than one in which pulses are statistically-significant intensity peaks, several studies (Liang & Kargatis 1996;Hakkila et al 2015Hakkila et al , 2018a have demonstrated that most pulses undergo and stretched at the time of reflection to show how well they match one another (the solid line represents the folded and stretched residuals preceding the time of reflection, while the dashed line represents the residuals following that time). The process used to identify time-reversality, as well as the fitted characteristics of this pulse, is described in Hakkila et al (2018b).…”
Section: Characteristics Of Grb Pulsesmentioning
confidence: 99%
See 2 more Smart Citations